The role of quarantine in plant germplasm introduction and exchange in Brazil Cenargen’s activities - Marques, Abi S. dos A.; Parente, Patrícia M. G.; Marinho, Vera Lúcia de A.; Buso, Gláucia S. C. (Pesquisa Agropecuaria Brasileira, 1995)
The most important aim of plant quarantine is to minimize the risk of entrance and spread of dangerous organisms into free areas. This activity is supported by national laws and based on biological principles. In Brazil, the quarantine of plant germplasm wich is introduced to support breeding programs, is carried out by a few institutions, including CENARGEN. Plant protection activities in Brazil began in 1909 and in 1934, the Plant Sanitary Defense Regulation was published. Those activities are conducted by the Ministry of Agriculture. Brazilian agriculture has historically depended on plant species of exotic origin, stressing the past and present importance of introducing plant genetic resources. Unfortunatelly, with the plant introductions, pathogens and insects have also been introduced, causing great losses. Plant germplasm introduction through CENARGEN has been made in accordance to the Brazilian phytosanitary legislation and conducted in a quarantine station. The phytosanitary analyses are performed using international methods and when some risky contamination is detected, appropriated eradicant treatment is applied. The quarantine procedures have been updated in order to adapt it to new situations. Also the interaction with the cooperators has been enhanced to keep all of them involved with the quarantine objective.